Psychological and pedagogical foundations of developing innovative thinking in future informatics teachers - Muxlisov Sodiqjon Saidjonovich (Goodwood Publishing, 2026)
Purpose: The study aims to examine the psychological and pedagogical foundations essential for developing innovative thinking in future computer science (informatics) teachers. It focuses on identifying key competencies such as creativity, cognitive flexibility, critical thinking, and adaptive problem-solving in the context of digital transformation in education. Research methodology: A mixed-methods approach was applied, combining qualitative and quantitative research. The study involved surveys, psychometric tests (e.g., Torrance Tests of Creative Thinking), interviews, focus groups, and classroom observations with a sample of 200 participants, including pre-service informatics teachers and faculty members. Data were analyzed using thematic analysis for qualitative inputs and statistical methods for quantitative data, ensuring triangulation for validity. Results: The findings indicate that innovative thinking in future informatics teachers is significantly influenced by a combination of psychological traits (such as self-regulation and intellectual curiosity), supportive pedagogical environments, and exposure to digital technologies. Effective development of innovative competencies requires integrated strategies involving experiential learning, reflective practices, and emotional intelligence training. The study recommends curriculum reforms, mentorship programs, and the use of digital tools to foster a culture of sustained innovation in teacher education.